A Dangerous Game - Graham, Heather (Toronto, Ontario, Canada : Mira, 2018)
"Wrapping up a normal day at the office, criminal psychologist Kieran Finnegan is accosted by a desperate woman who shoves an infant into her arms and then flees, only to be murdered minutes later on a busy Manhattan street ... Kieran cant stop thinking about the child and the victim, so her boyfriend, Craig Frasier, does what any good special agent boyfriend would do-- he gets the FBI involved ... Kieran wont sit idle when a lead surfaces through her familys pub. Investigating on her own, she uncovers a dangerous group that plays fast and loose with human lives and will stop at nothing to keep their secrets"--Provided by publisher.
Keywords: Women forensic scientists -- Fiction; Forensic psychology -- Fiction; Women -- Violence against; Fiction; Government investigators -- Fiction; Murder -- Investigation; Fiction; Human trafficking -- Fiction; New York (N.Y.) -- Fiction; Thrillers (Fiction)